2020
DOI: 10.1007/s11239-020-02086-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a rapid turn-over, fully-automated ADAMTS13 activity assay: a method comparison study

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a life-threatening thrombotic microangiopathy caused by severely reduced activity of the von-Willebrand factor-cleaving protease ADAMTS13, mainly caused by anti-ADAMTS-13 antibodies. Although several test systems for ADAMTS13 measurement exist, long turn-around times hamper the usability in daily practice. We performed a method comparison study for two commercially available ADAMTS13 assays and evaluated the agreement between the fully-automated rapid turn-over Hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 6 publications
3
21
2
Order By: Relevance
“…We are unsure why our study has uncovered a different pattern of bias between the HemosIL versus Technozym ADAMTS13 Activity assays as reported by Favresse et al, 20 and a higher level of bias to that reported by Valsecchi et al 21 and Stratmann et al 22 Differences may relate to study design and sample selection bias (ie, type of study performed, number and type of test samples assessed). The previous studies were all single‐center studies, and most testing appeared to reflect testing of stored, or retrospective samples, and so some potential for sample selection bias is inevitable.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…We are unsure why our study has uncovered a different pattern of bias between the HemosIL versus Technozym ADAMTS13 Activity assays as reported by Favresse et al, 20 and a higher level of bias to that reported by Valsecchi et al 21 and Stratmann et al 22 Differences may relate to study design and sample selection bias (ie, type of study performed, number and type of test samples assessed). The previous studies were all single‐center studies, and most testing appeared to reflect testing of stored, or retrospective samples, and so some potential for sample selection bias is inevitable.…”
Section: Discussioncontrasting
confidence: 56%
“…There are only three other reports on the HemosIL AcuStar ADAMTS13 Activity assay published in the literature 20‐22 . Favresse et al 20 reported on this assay in a 2018 study that described results of retrospective testing of 38 patient samples (8 TTP patients, 2 patients with moderate ADAMTS13 activity [>10%‐40%] and 28 patients with normal ADAMTS13 activity level [>40%] based on their routine assay [Technozym]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there were some discrepancies compared to FRET-VWF73 and a chromogenic activity ELISA, with some samples showing inter-assay disparity at normal and high activity, there was a good correlation between the assays and high agreement in classifying samples with ADAMTS13 levels below 10 IU/ dL. [34][35][36] Due to the reaction principle, these assays are not affected by icterus, lipaemia or plasma turbidity. However, the sample size in two of these studies was small and further evaluations may be needed before their widespread acceptance and regional regulatory bodies may require additional verification or validation procedures.…”
Section: Activity Assaysmentioning
confidence: 99%